Genome-Wide Identification and Analyses of Calmodulins and Calmodulin-like Proteins in Lotus japonicas - Liao, Jinqiu; Deng, Jiabin; Qin, Zongzhi; Tang, Jiayong; Shu, Maorong; Ding, Chunbang; Liu, Jing; Hu, Chao; Yuan, Ming; Huang, Yan; Yang, Ruiwu; Zhou, Yonghong (Frontiers in Plant Science, 2017)
L. japonicus, a model plant of legumes plants, is widely used in symbiotic nitrogen fixation. A large number of studies on it have been published based on the genetic, biochemical, structural studies. These results are secondhand reports that CaM is a key regulator during Rhizobial infection. In plants, there are multiple CaM genes encoding several CaM isoforms with only minor amino acid differences. Moreover, the regulation mechanism of this family of proteins during rhizobia infection is still unclear. In the current study, a family of genes encoding CaMs and CMLs that possess only the Ca2+-binding EF-hand motifs were analyzed. Using ML and BI tree based on amino acid sequence similarity, seven loci defined as CaMs and nineteen CMLs, with at least 23% identity to CaM, were identified. The phylogenetics, gene structures, EF hand motif organization, and expression characteristics were evaluated. Seven CaM genes, encoding only 4 isoforms, were found in L. japonicus. According to qRT-PCR, four LjCaM isoforms are involved in different rhizobia infection stages. LjCaM1 might be involved in the early rhizobia infection epidermal cells stage. Furthermore, additional structural differences and expression behaviors indicated that LjCMLs may have different potential functions from LjCaMs.